New Actors, New Political Spaces, Same Divided City? : Reflections on Poverty and the Politics of Urban Development in Salvador, Bahia /: Reflections on Poverty and the Politics of Urban Development in Salvador, Bahia. (September 2009) - Gledhill, John; Hita, Maria Gabriela
No abstract available